Model Kerja Sama Antarwilayah dalam Pengelolaan Daya Tarik Wisata Air Terjun Tumpak Sewu di Desa Sidomulyo, Kabupaten Lumajang - M. Daimul Abror; Imam Fachruddin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study explores the model of inter-regional cooperation in managing the Tumpak Sewu Waterfall tourist attraction, using three analytical lenses: legal-administrative, community politics, and inter-organizational politics. The research adopts a qualitative method with a case study design. Data were obtained through in-depth interviews, field observations, focus group discussions (FGDs), and document analysis. The data analysis follows the interactive model developed by Miles, Huberman, and Saldana, encompassing data reduction, data display, and conclusion drawing. Findings indicate that, from a legal-administrative perspective, a formal cooperation agreement between the Lumajang and Malang Regency Governments is urgently needed. The East Java Provincial Government is expected to facilitate this process to resolve ongoing jurisdictional disputes. From the community politics perspective, local stakeholders have demonstrated collective awareness and commitment to preserving and promoting the area's ecotourism potential. However, social tensions remain, particularly due to the dual ticketing practice, whereby visitors are charged both by the Sidomulyo Village Tourism Awareness Group (Pokdarwis) at the main entrance and by Sidorenggo residents at the base of the waterfall. From the perspective of inter-organizational politics, each regency government continues to pursue its institutional interests, preventing consensus on the administrative status of the Tumpak Sewu (also known as Coban Sewu) site. This lack of coordination has strained grassroots relations and hindered the implementation of integrated tourism management between the villages of Sidomulyo and Sidorenggo.